Routledge handbook of Indian politics - Kohli, Atul; Singh, Prerna 1979- (Routledge handbooks, 2013)
India's growing economic and socio-political importance on the global stage has triggered an increased interest in the country. This Handbook is a reference guide, which surveys the current state of Indian politics and provides a basic understanding of the ways in which the world's largest democracy functions. The Handbook is structured around four main topics: political change, political economy, the diversity of regional development, and the changing role of India in the world. Chapters examine how and why democracy in India put down firm roots, but also why the quality of governance offered by India's democracy continues to be low. The acceleration of economic growth since the mid-1980s is discussed, and the Handbook goes on to look at the political and economic changes in selected states, and how progress across Indian states continues to be uneven. It concludes by touching on the issue of India's international relations, both in South Asia and the wider world. The Handbook offers an invigorating initiation into the seemingly daunting and complex terrain of Indian politics. It is an invaluable resource for academics, researchers, policy analysts, graduate and undergraduate students studying Indian politics.